Graphene as Possible Reinforcement in Brass Material: A Short Overview - W.C. Yan, M.N. Masri, N.S. Alias, M. Mohamed, M. Yusoff and S. Mamat (International Journal of Advanced Science and Technology, 2020)
Copper alloy such as brass made from copper and zinc is a good alloy that have good properties to be utilized in various applications. The addition of alloying elements significantly enhances the properties of this alloys. In this study, the characterization of copper-zinc-graphene nanoflakes (Cu-Zn-GNF) as brass composite system is studied. Since graphene is a rising new material and lack of research information while leaded brass is less preferable option, therefore graphene is used as reinforcement.